Dinamika penegakan hukum di indonesia: Tantangan regulasi dan perlindungan hak asasi manusia - Syayyidah, Liza Elyvia Nur (Maliki Interdisciplinary Journal, 2025)
The dynamics of legal regulation in Indonesia are influenced by the diversity of legal sources and challenges in their application, including overlapping regulations between central and regional laws. This creates legal uncertainty that impacts the effectiveness of law enforcement and the protection of human rights (HAM). In this paper, the author uses the normative method, based on applicable laws and regulations, and conducts library research. The author uses secondary data as a normative research approach, which searches and uses library materials such as scientific writings and journals, books on law enforcement related to human rights as references, and studies human rights laws. Law enforcement in Indonesia faces various problems, such as corruption, political intervention, and low public legal awareness. State institutions, such as the National Human Rights Commission, play an important role in addressing these challenges, while civil society through Legal Aid Institutions also contribute to the defense of human rights. In conclusion, to improve the effectiveness of law enforcement and human rights protection, it is necessary to revamp the regulatory system, improve the integrity of law enforcement officials, and legal education for the public.